Respuesta :

Answer:

(3x − 4) (x − 2)

Step-by-step explanation:

Factor ax² + bx + c using the AC rule:

1) Multiply a and c.

2) Find factors of ac that add up to b.

3) Divide those factors by a and reduce the fractions.

4) The numerators become the constants, and the denominators become the coefficients.

Here, a = 3, b = -10, and c = 8.

1) ac = 24

2) Factors of 24 that add up to -10 are -4 and -6.

3) -4/3, -6/3 = -2/1

4) 3x − 4 and x − 2

Therefore, the factorization of 3x² − 10x + 8 is:

(3x − 4) (x − 2)